Computational self-awareness as design approach for visual sensor nodes - Guettatfi, Zakarya; Hübner, Philipp; Platzner, Marco; Rinner, Bernhard (12th International Symposium on Reconfigurable Communication-centric Systems-on-Chip (ReCoSoC))
Keywords: embedded systems; image sensors; power aware computing; wireless sensor networks; Zynq-based VSN node prototype; computational self-awareness; design approach; platform levels; power consumption; visual sensor networks; visual sensor nodes; Cameras; Hardware; Middleware; Multicore processing; Operating systems; Runtime; Reconfigurable platforms; distributed embedded systems; performance-resource trade-off; self-awareness; visual sensor nodes

How do students develop lexical means for understanding the concept of relative frequency? Empirical insights on the basis of trace analyses - Wessel, Lena (Proceedings of the Tenth Congress of the European Society for Research in Mathematics Education (CERME10, February 1 – 5, 2017))
Keywords: Academic language; relative frequency; scaffolding; design research; trace analysis

Advancing Research on Loyalty Programs: A Future Research Agenda. - Breugelmans, Els; Bijmolt, Tammo H A; Zhang, Jie; Basso, Leonardo J; Dorotic, Matilda; Kopalle, Praveen; Minnema, Alec; Mijnlieff, Willem Jan; Wünderlich, Nancy (Marketing Letters)
Despite the growing literature on loyalty program (LP) research, many questions remain underexplored. Driven by advancements in information technology, marketing analytics, and consumer interface platforms (e.g., mobile devices), there have been many recent developments in LP practices around the world. They impose new challenges and create exciting opportunities for future LP research. The main objective of this paper is to identify missing links in the literature and to craft a future research agenda to advance LP research and practice. Our discussion focuses on three key areas: (1) LP designs, (2) Assessment of LP performance, and (3) Emerging trends and the impact of new technologies. We highlight several gaps in the literature and outline research opportunities in each area.
Keywords: Loyalty programs; Loyalty program design; Loyalty program performance assessment; Emerging trends; Partnership loyalty programs; Customer relationship management

Wie kann über DBR die wissenschaftliche und praktische Relevanz der Forschung gesichert werden? - Brahm, Taiga; Jenert, Tobias
Auseinandersetzungen über Forschungsmethodologien haben in den Bildungswissenschaften lange Tradition. Sie werden häufig unversöhnlich und mit Profilierung der Gegensätze geführt. Für uns hängt die Sinnhaftigkeit einer Forschungskonzeption von der Problemstellung und dem Erkenntnisinteresse ab. Dies gilt auch für Design-Based Research (DBR). Dieser Ansatz entstand als Reaktion auf die Kritik an mangelnder praktischer Anwendung von Befunden aus der empirisch-analytischen Lehr-Lernforschung. Als Ergebnis werden Theorien angestrebt, die für die Praxis einen Nutzen bieten und zugleich über die Anwendung in einer singulären Situation hinausgehen. Wir wollen folgenden Fragen nachgehen: Wo liegen die Gemeinsamkeiten, wo die Spezifika von DBR gegenüber bestehenden Methodologien? Wie wird der Generalisierungsanspruch von Theorien innerhalb von DBR verstanden und umgesetzt? Für welche Erkenntnisinteressen eignet sich DBR? Welche Methoden sind für DBR sinnvoll und können wie angewendet werden?
Keywords: design-based research; gestatlungsbasierte Forschung; Erziehungswissenschaft; Design; Mixed Methods

Risk Reduction in Natural Disaster Management Through Information Systems: A Literature review and an IS design science research agenda - Schryen, Guido; Wex, Felix (International Journal of Information Systems for Crisis Response and Management (IJISCRAM))
Natural disasters, including earthquakes, Tsunamis, floods, hurricanes, and volcanic eruptions, have caused tremendous harm and continue to threaten millions of humans and various infrastructure capabilities each year. In their efforts to take countermeasures against the threats posed by future natural disasters, the United Nations formulated the ?Hyogo Framework for Action?, which aims at assessing and reducing risk. This framework and a global review of disaster reduction initiatives of the United Nations acknowledge the need for information systems research contributions in addressing major challenges of natural disaster management. In this paper, we provide a review of the literature with regard to how information systems research has addressed risk assessment and reduction in natural disaster management. Based on the review we identify research gaps that are centered around the need for acquiring general knowledge on how to design IS artifacts for risk assessment and reduction. In order to close these gaps in further research, we develop a research agenda that follows the IS design science paradigm.
Keywords: Natural Disaster Management; Risk Reduction; Hyogo Framework; IS Design Science; Literature review

A New Observation Model in the Logarithmic Mel Power Spectral Domain for the Automatic Recognition of Noisy Reverberant Speech - Leutnant, Volker; Krueger, Alexander; Haeb-Umbach, Reinhold (IEEE/ACM Transactions on Audio, Speech, and Language Processing)
In this contribution we present a theoretical and experimental investigation into the effects of reverberation and noise on features in the logarithmic mel power spectral domain, an intermediate stage in the computation of the mel frequency cepstral coefficients, prevalent in automatic speech recognition (ASR). Gaining insight into the complex interaction between clean speech, noise, and noisy reverberant speech features is essential for any ASR system to be robust against noise and reverberation present in distant microphone input signals. The findings are gathered in a probabilistic formulation of an observation model which may be used in model-based feature compensation schemes. The proposed observation model extends previous models in three major directions: First, the contribution of additive background noise to the observation error is explicitly taken into account. Second, an energy compensation constant is introduced which ensures an unbiased estimate of the reverberant speech features, and, third, a recursive variant of the observation model is developed resulting in reduced computational complexity when used in model-based feature compensation. The experimental section is used to evaluate the accuracy of the model and to describe how its parameters can be determined from test data.
Keywords: computational complexity; reverberation; speech recognition; automatic speech recognition; background noise; clean speech; computational complexity; energy compensation; logarithmic mel power spectral domain; mel frequency cepstral coefficients; microphone input signals; model-based feature compensation schemes; noisy reverberant speech automatic recognition; noisy reverberant speech features; reverberation; Atmospheric modeling; Computational modeling; Noise; Noise measurement; Reverberation; Speech; Vectors; Model-based feature compensation; observation model for reverberant and noisy speech; recursive observation model; robust automatic speech recognition

Wissenschafts-Praxis-Kooperation in designbasierter Forschung: Im Spannungsfeld zwischen wissenschaftlicher Gültigkeit und praktischer Relevanz - Brahm, Taiga; Jenert, Tobias (Zeitschrift für Berufs-und Wirtschaftspädagogik-Beihefte (ZBW-B))
Designbasierte Forschung zielt darauf, praktische Problemstellungen zu lösen und gleichzeitig wissenschaftliche Theorien (weiter) zu entwickeln. Dabei durchläuft designbasierte Forschung in der Regel die Phasen der Problemdefinition, der Entwicklung eines didaktischen Designs, der zyklischen Design-Implementation sowie der Evaluation und Reflexion in enger Kooperation von Wissenschaft und Praxis. Inwieweit es mittels designbasierter Forschung gelingen kann, wissenschaftliche Gültigkeit und praktische Relevanz von Forschung gleichermassen zu steigern, wird im Beitrag anhand des Konzepts multipler Signifikanzen erörtert. Dabei wird diskutiert, wie die Gestaltung der Kooperation von Forschenden und Praktikern/-innen dazu beitragen kann, die praktische, statistische, klinische und wirtschaftliche Signifikanz des designbasierten Forschungsprozesses sicherzustellen.
Keywords: Design-based research; design research; validity; significance; Bildungsforschung; designbasierte Forschung; Wissenschafts-Praxis-Kommunikation

An Assisted Single Source Verification Metric Model Code Generation Methodology - Kuznik, Christoph; Müller, Wolfgang; Defo, Gilles Bertrand
The ever-increasing complexity of heterogeneous electronic systems demand for intensified abstraction and automation efforts to improve design, verification and validation productivity, especially in earlier phases of system engineering. Within the verification activity various metrics can be applied to determine functional correctness or the overall progress. Here, a supporting verification methodology defining high-level verification planning down to the actual metric code development is essential. Moreover, an advanced assistance for the designer, such as a tooling infrastructure to automatize and accelerate the metric code implementation, is needed to minimize the influence of errorprone manual coding. In this article we present a single-source verification metric code-generation methodology for improved coverage automation. We determine (i) a suitable metric model for model-based capture of verification metrics as well as (ii) an assisted model-based processing and generation flow of the verification environment and metric skeletons. We apply our method to a SystemC case-study, in doing so, targeting metric code implementation productivity and consistency enhancement.
Keywords: System Design; Verification

Fast and Open Virtual Platforms for TriCore-based SoCs Using QEMU - Koppelmann, Bastian; Messidat, Bernd; Becker, Markus; Müller, Wolfgang; Scheytt, J. Christoph (Proceedings of the Design and Verification Conference Europe (DVCON Europe))
In this paper, we present an efficient approach to virtual platform modeling for TriCore-based SoCs by combining fast and open software emulation with IEEE-1666 Standard SystemC simulation. For evaluation we consider Infineon's recently introduced AURIX processor family as a target platform, which utilizes multiple CPU cores operating in lockstep mode, memories, hierarchical buses, and a rich set of peripherals. For SoC prototyping, we integrate the fast and open instruction accurate QEMU software emulator with the TLMu library for SystemC co-verification. This article reports our most recent efforts of the implementation of the TriCore instruction set for QEMU. The experimental results demonstrate the functional correctness and performance of our TriCore implementation.
Keywords: System Design; Verification

Encouraging Family and Parent Education: Program Development and Evaluation in the Federal State of Baden-Württemberg, Germany - Landhäußer, Sandra; Faas, Stefan; Treptow, Rainer (Center for Educational Policy Studies Journal (CEPS))
Against the background of a European-wide strategy of governance aimed at improving support for parents and families, the following report details the conceptualization and evaluation of a federal state program4 in Baden- Württemberg (Germany) which was launched in 2008 to encourage fam- ily and parent education. Two program components, a voucher system for parents with a new-born child and an element that emphasizes educa- tional offers for families with special needs in particular living situations, were started to increase requests for educational courses. The aim was to establish and deepen cooperation between different public and private professional services that are in contact with parents and their children. The results show that main goals of the program were reached.
Keywords: family and parent education; cooperation; voucher system; support for families with special needs in particular living situations; program evaluation

Fast and Open Virtual Platforms for TriCore-based SoCs Using QEMU - Koppelmann, Bastian; Messidat, Bernd; Kuznik, Christoph; Müller, Wolfgang; Becker, Markus; Scheytt, J. Christoph (Proceedings of the Design and Verification Conference Europe (DVCON Europe))
In this paper, we present an efficient approach to virtual platform modeling for TriCore-based SoCs by combining fast and open software emulation with IEEE-1666 Standard SystemC simulation. For evaluation we consider Infineon's recently introduced AURIX processor family as a target platform, which utilizes multiple CPU cores operating in lockstep mode, memories, hierarchical buses, and a rich set of peripherals. For SoC prototyping, we integrate the fast and open instruction accurate QEMU software emulator with the TLMu library for SystemC co-verification. This article reports our most recent efforts of the implementation of the TriCore instruction set for QEMU. The experimental results demonstrate the functional correctness and performance of our TriCore implementation.
Keywords: System Design; Verification

Reflection, abstraction and theorizing in design and development research - Gregor, Shirley; Müller, Oliver; Seidel, Stefan (European Conference on Information Systems)
Keywords: Abstraction; Affordances; Design Science Research; Design Theory; Information Systems Development; Reflection; Theorizing

Designing interaction routines in service networks: A modularity and social construction-based approach - Becker, Jörg; Beverungen, Daniel; Knackstedt, Ralf; Matzner, Martin; Müller, Oliver; Pöppelbuss, Jens (Scandinavian Journal of Information Systems)
Keywords: Business process management; Conceptual modeling; Interaction routines; Modular design; Service networks; Social construction

Dynamic reliability management: Reconfiguring reliability-levels of hardware designs at runtime - Anwer, Jahanzeb; Meisner, Sebastian; Platzner, Marco (Reconfigurable Computing and FPGAs (ReConFig), 2013 International Conference on)
Keywords: fault tolerant computing; field programmable gate arrays; logic design; reliability; BYU-LANL tool; DRM tool flow; FPGA based hardware designs; avionic application; device technologies; dynamic reliability management; fault-tolerant operation; hardware designs; reconfiguring reliability levels; space applications; Field programmable gate arrays; Hardware; Redundancy; Reliability engineering; Runtime; Tunneling magnetoresistance

Bayesian Feature Enhancement for Reverberation and Noise Robust Speech Recognition - Leutnant, Volker; Krueger, Alexander; Haeb-Umbach, Reinhold (IEEE Transactions on Audio, Speech, and Language Processing)
In this contribution we extend a previously proposed Bayesian approach for the enhancement of reverberant logarithmic mel power spectral coefficients for robust automatic speech recognition to the additional compensation of background noise. A recently proposed observation model is employed whose time-variant observation error statistics are obtained as a side product of the inference of the a posteriori probability density function of the clean speech feature vectors. Further a reduction of the computational effort and the memory requirements are achieved by using a recursive formulation of the observation model. The performance of the proposed algorithms is first experimentally studied on a connected digits recognition task with artificially created noisy reverberant data. It is shown that the use of the time-variant observation error model leads to a significant error rate reduction at low signal-to-noise ratios compared to a time-invariant model. Further experiments were conducted on a 5000 word task recorded in a reverberant and noisy environment. A significant word error rate reduction was obtained demonstrating the effectiveness of the approach on real-world data.
Keywords: Bayes methods; compensation; error statistics; reverberation; speech recognition; Bayesian feature enhancement; background noise; clean speech feature vectors; compensation; connected digits recognition task; error statistics; memory requirements; noisy reverberant data; posteriori probability density function; recursive formulation; reverberant logarithmic mel power spectral coefficients; robust automatic speech recognition; signal-to-noise ratios; time-variant observation; word error rate reduction; Robust automatic speech recognition; model-based Bayesian feature enhancement; observation model for reverberant and noisy speech; recursive observation model

Conceptual Design of Advanced Condition Monitoring for a Self-Optimizing System based on its Principle Solution - Sondermann-Wölke , Christoph; Meyer, Tobias; Dorociak, Rafal; Gausemeier, Jürgen; Sextro, Walter (Proceedings of the 11th International Probabilistic Safety Assessment and Management Conference (PSAM11) and The Annual European Safety and Reliability Conference (ESREL2012))
The rapid development of communication and information technology opens up fascinating perspectives, which go far beyond the state of the art in mechatronics: mechatronic systems with inherent partial intelligence. These so called self-optimizing systems adapt their objectives and behavior autonomously and flexibly to changing operating conditions. On the one hand, securing the dependability of such systems is challenging due to their complexity and non-deterministic behavior. On the other hand, self-optimization can be used to increase the dependability of the system during its operation. However, it has to be ensured, that the self-optimization works dependable itself. To cope with these challenges, the multi-level dependability concept was developed. It enables predictive condition monitoring, influences the objectives of the system and determines suitable means to improve the system's dependability during its operation. In this contribution we introduce a procedure for the conceptual design of an advanced condition monitoring based on the system's principle solution. The principle solution describes the principal operation mode of the system and its desired behavior. It is modeled using the specification technique for the domain-spanning description of the principle solution of a self-optimizing system and consists of a coherent system of eight partial models (e.g. requirements, active structure, system of objectives, behavior, etc.). The partial models are analyzed separately in order to derive the components of the multi-level dependability concept. In particular, the reliability analysis of the partial model active structure is performed to identify the system elements to be monitored and parameters to be measured. The principle solution is extended accordingly: e.g. with system elements required for the realization of the dependability concept. The advantages of the method are shown on the self-optimizing guidance module of a railroad vehicle.
Keywords: Mechatronic Systems; Principle Solution; Condition Monitoring; Conceptual Design

A Statistical Observation Model For Noisy Reverberant Speech Features and its Application to Robust ASR - Leutnant, Volker; Krueger, Alexander; Haeb-Umbach, Reinhold (Signal Processing, Communications and Computing (ICSPCC), 2012 IEEE International Conference on)
In this work, an observation model for the joint compensation of noise and reverberation in the logarithmic mel power spectral density domain is considered. It relates the features of the noisy reverberant speech to those of the non-reverberant speech and the noise. In contrast to enhancement of features only corrupted by reverberation (reverberant features), enhancement of noisy reverberant features requires a more sophisticated model for the error introduced by the proposed observation model. In a first consideration, it will be shown that this error is highly dependent on the instantaneous ratio of the power of reverberant speech to the power of the noise and, moreover, sensitive to the phase between reverberant speech and noise in the short-time discrete Fourier domain. Afterwards, a statistically motivated approach will be presented allowing for the model of the observation error to be inferred from the error model previously used for the reverberation only case. Finally, the developed observation error model will be utilized in a Bayesian feature enhancement scheme, leading to improvements in word accuracy on the AURORA5 database.
Keywords: Robust Automatic Speech Recognition; Bayesian feature enhancement; observation model for reverberant and noisy speech

Mutation-Analysis Driven Functional Verification of a Soft Microprocessor - Xie, Tao; Müller, Wolfgang; Letombe, Florian (Proceedings of SOCC2012)
This paper proposes a quality driven, simulation based approach to functional design verification, which applies mainly to IP-level HDL designs with well specified test instruction format and is evaluated on a soft microprocessor core MB-LITE [5]. The approach utilizes mutation analysis as the quality metric to steer an automated simulation data generation process. It leads to a simulation flow with two phases towards an enhanced mutation analysis result. First in a random simulation phase, an in-loop heuristics is deployed and adjusts dynamically the test probability distribution so as to improve the coverage efficiency. Next, for each remaining hard-to-kill mutant, a search heuristics on test input space is developed to iteratively locate a target test, using a specific objective cost function for the goal of killing HDL mutant. The effectiveness of this integrated two-phase simulation flow is demonstrated by the results with the MB-LITE microprocessor IP.
Keywords: Analytical models; Hardware design languages; Microprocessors; Cost function; Data models; Search problems; IP networks

Towards Multilingual Biographical Event Extraction - Geierhos, Michaela; Bouraoui, Jean-Leon; Watrin, Patrick (Multilingual Resources, Multilingual Applications. Proceedings of the Conference of the German Society for Computational Linguistics and Language Technology (GSCL) 2011)
Within this paper, we describe the special requirements of a semantic annotation scheme used for biographical event extraction in the framework of the Europeancollaborative research project Biographe. This annotationscheme supports interlingual search for people due to its multilingual support covering four languages such as English, German, French and Dutch.
Keywords: Biographical Event Extraction for Interlingual People Search; Semantic Annotation Scheme

Leaving the Beaten Tracks in Creative Work – A Design Theory for Systems that Support Convergent and Divergent Thinking - Müller-Wienbergen, Felix; Müller, Oliver; Seidel, Stefan; Becker, Jörg (Journal of the Association for Information Systems)
Keywords: Creativity; Creativity Support Systems; convergent thinking; design theory; divergent thinking